Measurable Changes in Hydronephrosis During Pregnancy Induced by Positional Changes: Ultrasonic Assessment and its Diagnostic Implication - Rajaei Isfahani, Mohammad; Haghighat, Mehdi (Urology Journal, 2009)
Introduction: Unilateral or bilateral dilation of the ureters occurs commonly during pregnancy. Ultrasonography is a suitable diagnostic method for hydronephrosis; however, it cannot differentiate obstructive from nonobstructive hydronephrosis. Our aim was to evaluate measurable changes in hydronephrosis induced by a mother’s positional changes using ultrasonography to differentiate hydronephrosis during pregnancy from pathologic etiologies. Materials and Methods: Pregnant women presenting for routine ultrasonography were enrolled in this study. A patient history was taken, and a physical examination was performed. Ultrasonography was performed to determine gestational age, parity, fetal presentation, presence or absence of hydramnios, and hydronephrosis and its severity. Thirty minutes after changing position (flank position or on all fours), patients were reevaluated by ultrasonography to determine the severity of hydronephrosis. Results: Of 59 pregnant women with an average age of 25.4 years, 33 (55.9%) had no urinary complaint during pregnancy. Forty-one women (69.5%) had hydronephrosis, 24 (58.5%) of whom only in right kidney. The severity of hydronephrosis in one kidney was related with the severity of hydronephrosis in the other kidney (P = 0.007). Fetal presentation and gestational age were not associated with hydronephrosis. Risk of hydronephrosis was higher in the first pregnancy (likelihood ratio = 6.8, P = 0.009). Thirty minutes after changing positions, the anteroposterior pelvis diameter significantly decreased in the right and left kidneys (P = 0.004, P = 0.001). Conclusion: Ultraonography in two steps with positional change (dynamic ultrasonography) may be used to differentiate hydronephrosis of pregnancy from other pathologies.